The Outcome of Thoracentesis versus Chest Tube Placement for Hepatic Hydrothorax in Patients with Cirrhosis: A Nationwide Analysis of the National Inpatient Sample - Ali Ridha; Yasir Al-Abboodi; Matthew Fasullo (Gastroenterology Research and Practice)
There are only a few studies with a small sample size of patients that have compared the risks of using chest tubes versus thoracentesis in hepatic hydrothorax. It has been shown that many complications may arise secondary to chest tube placement and is associated with increased morbidity and mortality. In this retrospective study, patients with cirrhosis were identified from the 2009 National Inpatient Sample by using ICD-9 codes; we evaluated the risk of chest tube versus thoracentesis in a largest population with hepatic hydrothorax to date to measure the mortality and the length of stay. A total of 140,573 patients with liver cirrhosis were identified. Of this, 1981 patients had a hepatic hydrothorax and ended up with either thoracentesis (1776) or chest tube (205). The mortality in those who received a chest tube was two times higher than that in thoracentesis group with a P value of ≤0.001 (CI 1.43–312). In addition, the length of hospital stay of the chest tube group was longer than that of the thoracentesis subset (7.2 days versus 3.8 days, resp.). We concluded that chest tube placement has two times higher mortality rate and longer hospital length of stay when compared to patients who underwent thoracentesis.